Costs associated with influenza-related hospitalization in the elderly - Núria Torner; Encarna Navas; Núria Soldevila; Diana Toledo; Gemma Navarro; Aurea Morillo; Maria José Pérez; Angela Domínguez; the Working Group of the Project PI12/02079 (Taylor & Francis Group, 2017)
Seasonal influenza epidemics remain a considerable burden in adults, especially in those at higher risk of complications. The aim of this study was to determine the costs associated with influenza-related hospitalization in patients aged ≥65 y admitted to 20 hospitals from 7 Spanish regions during the 2013-14 and 2014-15 influenza seasons. Bivariate analysis was used to compare costs in vaccinated and unvaccinated cases. Costs were calculated according to the Spanish National Health System diagnosis-related group tables for influenza and other respiratory system conditions (GRD 89 and GRD 101). A total of 728 confirmed influenza cases were recorded: 52.9% were male, 46.7% were aged 75-84 years, and 49.3% received influenza vaccine ≥15 d prior to hospital admission. Influenza-related mean hospitalization costs (MHC) were € 1,184,808 in unvaccinated and € 1,152,333 in vaccinated cases (2.75% lower). Influenza vaccination showed significant protection against ICU admission (OR 0.35, 95%CI 0.21-0.59; p < 0001); mechanical ventilation (OR 0.56, 95%CI 0.39-0.80; p = 0.002); secondary bacterial pneumonia (OR 0.61, 95%CI 0.39-0.98; p = 0.04) and a higher degree of dependence (OR 0.74, 95%CI 0.55-0.99; p = 0.04). No association was observed for the Charlson comorbidity index or the mean hospital stay. Although influenza vaccination of the elderly may not achieve significant savings in mean hospitalization costs, it may lessen the degree of severity and avoid complications.